The Lebesgue Measure on Rn. (2015) - Mărginean, Diana
Abstract: Lebesgue measure on R n is restriction of outer Lebesgue measure to the family of Lebesgue measurable sets. All properties of Lebesgue positive measure on R are transfered to Lebesgue measure on R n . The Lebesgue measure on B is only meassure defined on σ-algebra of Borel sets of R n, which is invariance to translation and .